ALMA molecular observations of supernova 1987A. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Matsuura, Mikako; Indebetouw, R.; Kamenetzky, J.; McCray, R.
Abstract: Twenty-six years after the explosion, we conducted a molecular line survey for supernova 1987A, using the ALMA observatory. The detection of molecules in the ejecta can uncover evidence of mixing and dynamics in the early days after the supernova explosion, as well as of molecular chemistry that took place in the last 25 years. It is still not well understood to what extent the macroscopic mixing occurred after the supernova explosion. Molecules can provide a new tool to probe and test the extent of mixing: macroscopic mixings stir the elements from different layers of nuclear-reaction zones in the stellar core, opening the possibilities to form molecules that were composed of elements from different nuclear-burning zones, which the ALMA can detect. Additionally, the ALMA measured the line profiles of molecules, which unveiled the dynamics of ejecta. The high sensitivity observations of molecules can open a new window to determine SN explosion mechanisms and allow us to probe macroscopic mixing after the explosion.